TEMPORARY SERIES OF HEAT SOURCES IN MESOREGIONS OF PARAÍBA, BRAZIL - Novais, Danilo Brito; Souto, Patrícia Carneiro; Souto, Jacob Silva; Santana, José Augusto da Silva (Floresta, 2019)
The management of fire is a set of decisions directed to practices of prevention, verification and control of this agent that can modify the landscape. Remote sensing helps in understanding the phenomena that occur on the earth's surface. This work had the objective of analyzing the occurrences of heat sources recorded by satellites in the State of Paraíba (2000 – 2015). The occurrences of heat sources were selected by months of the year making it possible to visualize the frequency of heat sources in different locations. It is observable that the years with the highest number of heat sources in Paraíba were 2003, 2004 and 2009. In the six municipalities studied, 3.712 heat sources were recorded, with Cajazeiras municipality having the highest number of records (2.253 occurrences). It is concluded that the highest occurrence of heat sources inthe studied regions runs from September to December, where the Sertão Paraibano mesoregion was the one with the highest incidence of heat sources, being the most affected by fire. It is recommended, thus,the implementation of awareness programs that inform the citizens of rural and urban areas about the importance of adequate fire management in order to reduce heat sources in the region.